Simulation of suspended sediment and black carbon transport in surface water layer of Ha Long bay - Cuong, Le Duc; Thao, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
Delft3D model employed to simulate the distribution and transport of suspended sediment and black carbon in Ha Long bay shows outcomes meeting with results from previous experiment studies. In the rainy season, suspended matter in surface layer is mainly in waters of western and southwestern Cat Ba island regions, and from Cua Luc toward the south nearshore areas with concentration of 50–130 g/m3. The concentration of suspended setdiment in the waters from Cua Luc to the north nearshore area is from 20 g/m3 to 50 g/m3 and that of offshore areas is 2–20 g/m3. In the dry season, the average concentrations of suspended matter are lower, approximately 110–150 g/m3 compared to the rainy season. In the rainy season, the total particulate carbon in surface layer is 0.0016–0.0028 kg/m3 and in the dry season, it ranges from 0.0001–0.005 kg/m3.